EM ALGORITHM FOR SOLVING THE STOCHASTIC ASSEMBLY LINE BALANCING PROBLEM - Gu, Liya; Hennequin, Sophie; Sava, Alexandru; Xie, Xiaolan (IFAC Proceedings Volumes, 2006)
In this paper, a new methodology electromagnetism- like mechanism (EM) is used to solve the stochastic type II assembly line balancing problem. This NP-hard problem consists in assigning assembly activities to a given number of workstations of an assembly line in order to minimize the cycle time subject to precedence constraints. The operation times for each assembly activities are random. The solution methodology is a new EM algorithm which uses a random key to each activity and assigns them to workstations according to the random key and a heuristic EM outperforms simulated annealing (SA) for large scaled problems.